2002
DOI: 10.1080/00288330.2002.9517133
|View full text |Cite
|
Sign up to set email alerts
|

Lipid content in rainbow trout (Oncorhynchus mykiss) fry and parr reared in spawning tributaries of Lake Taupo, New Zealand

Abstract: The total lipid content of fry (25-30 mm) and parr (55-110 mm) of rainbow trout (Oncorhynchus mykiss Richardson 1836) was measured in spring 1996 and 1997 and in autumn 1997 in six trout-rearing tributaries of Lake Taupo, New Zealand. The fat content of fry was variable between streams and some streams had a higher inter-annual variation than others. The fat content of parr was also variable among streams but no difference could be found between seasons. The streams that produced fry with high fat content di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
1
9
0
Order By: Relevance
“… b Daphnia magna critical body burden conversions from wet weight to per total lipid basis were obtained from Dedual [43] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… b Daphnia magna critical body burden conversions from wet weight to per total lipid basis were obtained from Dedual [43] …”
Section: Resultsmentioning
confidence: 99%
“…Pond snail Mixed types 9 [22] a Lipid fraction of 2.90% was assumed for O. mykiss [42]. b Daphnia magna critical body burden conversions from wet weight to per total lipid basis were obtained from Dedual [43]. c Chlorella pyrenoidosa data was used in lieu of C. vulgaris.…”
Section: Lymnaea Stagnalismentioning
confidence: 99%
“…The influence of distinct fluvial habitat types over smaller spatial scales is however less documented. Similarly, other studies have reported differences in lipid content of rainbow trout juveniles (Oncorhynchus mykiss Walbaum) reared in different tributaries (Dedual 2002) and of juvenile Atlantic salmon originating from sites differing in water temperature (Berg et al 2006). Interesting trends in the body composition were observed but our initial hypothesis, that fish of the upstream sections have higher energy content, was nevertheless not verified.…”
Section: Introductionmentioning
confidence: 61%
“…For juvenile salmonids, energy acquired through feeding is allocated for processes such as maintenance, somatic growth, overwinter survival and early maturation or smoltification (Jonsson & Jonsson 1998;Post & Parkinson 2001;Morgan et al 2002;Dempson et al 2004). Proximate body composition is the direct consequence of the allometric relationships of feeding and metabolism, the activity levels, life-history strategy and the spatio-temporal variations in biotic and abiotic factors (Gardiner & Geddes 1980;Berg & Bremset 1998;Jonsson & Jonsson 1998;Dedual 2002;Morgan et al 2002;Dempson et al 2004;Berg et al 2006). The influence of seasonal variations of these factors is especially evident in temperate and sub-Arctic regions where lipids are stored during summer to be mobilised during winter when food is scarce (Gardiner & Geddes 1980;Berg & Bremset 1998;Finstad et al 2004;Naesje et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation